2018
DOI: 10.3311/ppci.11601
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Vibration Control of Seismically Excited Civil Structures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Thus, it is conventionally required that the extreme response of building structures be restricted within an acceptable level [31,32]. Otherwise, associated measures should be implemented for vibration reduction and control of the dynamic systems [33][34][35][36].…”
Section: Estimation Of Structural Extreme Responsementioning
confidence: 99%
“…Thus, it is conventionally required that the extreme response of building structures be restricted within an acceptable level [31,32]. Otherwise, associated measures should be implemented for vibration reduction and control of the dynamic systems [33][34][35][36].…”
Section: Estimation Of Structural Extreme Responsementioning
confidence: 99%
“…Grimaz and Malisan [22] showed that near-field and far-field ground motion are different in intensity, nature, and typology and suggested different scale factors for near-field and far-field ground motions. Pnevmatikos et al [23,24] studied the seismic responses of offshore platforms subjected to near-field ground motions with distinct pulses, and taking into account the pile-soil-structure interaction effects. The offshore platforms, which were steel structures and located in a sea region, were similar to container crane structures.…”
Section: Introductionmentioning
confidence: 99%
“…Seleemah et al [45] applied ANN to predict the maximum shear strength of concrete beams without horizontal reinforcement. Blachowski and Pnevmatikos [46] have developed a vibration control system based on the ANN method, for application in earthquake engineering. As an example for structural engineering, Kiani et al [47] have applied AI techniques including support vector machines (SVM) and ANN for deriving seismic fragility curves.…”
Section: Introductionmentioning
confidence: 99%